Analisis Fraud Diamond Theory dalam Pengelolaan Dana Desa - Mukhlas Adi Putra; Frida Widyawati Triasningrum; Sarastanto Aulia Heru Pranoto (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
This article defines that Fraud Diamond Theory is a tool to detect acts of fraud that occur in the use of village funds in Guntur Regency, Demak Regency. Proxies used in Fraud Diamond Theory are transparency on the pressure variable, ineffective monitoring on the opportunity variable, external audit quality on the rationalization variable, and positioning on the ability variable. The population in this study were all village officials found in Guntur District. The method used is nonprobability sampling and sampling cuota. There are 18 villages in Guntur District and 10 villages will be given 10 copies of each questionnaire. The questionnaire returned 153 copies of the 180 distributed questionnaires. Multiple linear regression was used in the analysis of test data with the help of the SPSS Version 21 software program. This study found that pressure and rationalization did not significantly affect fraud detection. Whereas opportunity and capability will significantly influence fraud detection on the use of village funds